Co-Implications: Rethinking the Relationship Between Psychoanalysis, Literature, and Philosophy - Isabelle Alfandary; Michael Levine; Alessia Ricciardi (Humanities)
Psychoanalysis, literature, and philosophy—these practices and disciplines are linked by a dual paradigm of affinity and asymmetry [...]